2014
DOI: 10.1007/978-3-319-09614-8_14
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Metabolism by Oral Streptococci and Interaction with Human Papillomavirus Leads to Malignant Transformation of Oral Keratinocytes

Abstract: Poor oral hygiene, ethanol consumption, and human papillomavirus (HPV) are associated with oral and esophageal cancers. However, the mechanism is not fully known. This study examines alcohol metabolism in Streptococcus and its interaction with HPV-16 in the malignant transformation of oral keratinocytes. The acetaldehyde-producing strain Streptococcus gordonii V2016 was analyzed for adh genes and activities of alcohol and aldehyde dehydrogenases. Streptococcus attachment to immortalized HPV-16 infected human o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
2
2
0
Order By: Relevance
“…In addition, few studies have investigated the relationship between HPV and microbial communities in the hypopharynx. In our study, the HPV-positive cohort was proven to have an increased abundance of specific microbes, particularly Streptococcus , consistent with other studies [ 25 , 26 ]. Streptococcus promotes HPV infection by expressing furin-like peptidases and is involved in ethanol metabolism, resulting in carcinogenesis [ 25 , 26 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, few studies have investigated the relationship between HPV and microbial communities in the hypopharynx. In our study, the HPV-positive cohort was proven to have an increased abundance of specific microbes, particularly Streptococcus , consistent with other studies [ 25 , 26 ]. Streptococcus promotes HPV infection by expressing furin-like peptidases and is involved in ethanol metabolism, resulting in carcinogenesis [ 25 , 26 ].…”
Section: Resultssupporting
confidence: 92%
“…In our study, the HPV-positive cohort was proven to have an increased abundance of specific microbes, particularly Streptococcus , consistent with other studies [ 25 , 26 ]. Streptococcus promotes HPV infection by expressing furin-like peptidases and is involved in ethanol metabolism, resulting in carcinogenesis [ 25 , 26 ]. According to our results, patients with different abundances of key taxa presented different prognoses, indicating that the abundances of the two screened genera enable better prediction of recurrence in HPSCC patients than clinical variables, leading to the conclusion that microbiota examination may be an encouraging approach for clinical application.…”
Section: Resultssupporting
confidence: 92%
“…In our previous publications, we reported that Streptococcus promotes HPV16 entry into oral keratinocytes and oral squamous cell carcinoma cells. These suggest a possible interplay for Streptococcus and other similar bacteria to contribute to HPV16 entry (Schwartz et al., ; Tao, Pavlova, Gasparovich, Jin, & Schwartz, ). It is, therefore, reasonable to investigate how these microorganisms could play a role in determining HPV tissue tropism, and subsequently, how they might contribute to the development of tissue‐specific neoplasia.…”
Section: Introductionmentioning
confidence: 99%
“…Other co-factors that have been implicated thus far include UV-exposure [11] and HCV infections [12]. Furthermore, in vitro cell culture studies using oral keratinocytes showed co-operation between HPV and tobacco carcinogens [13][14][15], alcohol metabolism by streptococci [16], and EBV-co-infections [17,18]. Early diagnosis of HPV-HNSCC in patients is challenging due to patients often first presenting at the clinic with a neck mass representing an advanced stage of disease [19].…”
mentioning
confidence: 99%